PENGARUH BAHAN ORGANIK TERHADAP BEBERAPA SIFAT KIMIA TANAH PADA LAHAN KERING MASAM - Iwandikasyah Putra; Muhammad Jalil (Jurnal Agrotek Lestari, 2018)
Acidic dry land generally has poor chemical elements, such as high Al content, low organic matter content, low nutrient content, especially N, P, K, Ca, and Mg, and low pH. This study was conducted to assess the effect of organic matter on soil chemical elements on dry land in the district Ingin Jaya, Aceh Besar. This research using randomized block design (RBD) non factorial with three replications. The factors that studied are organic materials include: compost (B1), manure (B2), and green manure (B3). The results showed that added of compost, manure, and green manure with a dose of 20 tons per hectare is very significantly increased P-available, significantly increasing the pH and C organic, and the effect is not significant to the CEC, N-total. The highest content of P-available, pH, and C-Organic are found in the treatment of organic compost.Keywords: Acidic dry land, organic matter, soil chemical properties.